Advances in diagnosis, management, and long-term outcomes of pediatric vasovagal syncope: a comprehensive review - Zhu, Wenjing; Bian, Xueyan; Lv, Jianli (Frontiers in Cardiovascular Medicine, 2025)
Vasovagal syncope (VVS) is the most common cause of transient loss of consciousness in children and adolescents, accounting for 60%–80% of syncope cases. This review synthesizes current evidence on pediatric VVS, focusing on advances in diagnosis, management, and long-term outcomes. Through a comprehensive literature search of studies published between 2001 and 2024, we analyzed epidemiological patterns, pathophysiological mechanisms, diagnostic approaches, management strategies, and prognostic factors. Recent diagnostic advances include implantable loop recorders and smartphone applications, which have improved diagnostic accuracy. Management has evolved toward individualized approaches, emphasizing non-pharmacological interventions (hydration, salt supplementation, physical counterpressure maneuvers) as first-line treatment, with medications such as midodrine and fludrocortisone showing variable efficacy in refractory cases. Long-term studies indicate that while most children experience improvement over time, 33%–50% have recurrent episodes within three years, with factors such as lower mean arterial pressure, higher urine specific gravity, younger age, family history of syncope, and lower body mass index associated with increased recurrence risk. Though generally benign, VVS can significantly impact quality of life and carries substantial psychosocial consequences. Future research should focus on developing predictive models for recurrence risk and exploring personalized treatment approaches to improve outcomes.